2017
DOI: 10.1371/journal.ppat.1006145
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 Enhances the Antiviral Action of Zinc-Finger Antiviral Protein (ZAP)

Abstract: The host factor and interferon (IFN)-stimulated gene (ISG) product, zinc-finger antiviral protein (ZAP), inhibits a number of diverse viruses by usurping and intersecting with multiple cellular pathways. To elucidate its antiviral mechanism, we perform a loss-of-function genome-wide RNAi screen to identify cellular cofactors required for ZAP antiviral activity against the prototype alphavirus, Sindbis virus (SINV). In order to exclude off-target effects, we carry out stringent confirmatory assays to verify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
253
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(280 citation statements)
references
References 57 publications
17
253
0
Order By: Relevance
“…5). During the course of this work, Li et al reported that TRIM25-mediated ubiquitination was essential for ZAP (33). Our results reported here are consistent with theirs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…5). During the course of this work, Li et al reported that TRIM25-mediated ubiquitination was essential for ZAP (33). Our results reported here are consistent with theirs.…”
Section: Discussionsupporting
confidence: 93%
“…Very recently, Li et al reported that TRIM25 mediated ZAP ubiquitination and synergized with ZAP to inhibit Sindbis virus replication (33). In the present study, we confirmed their results that TRIM25 is required for the antiviral activity of ZAP.…”
supporting
confidence: 91%
See 3 more Smart Citations